Temporal Profiling of Extracellular Polymeric Substances Associated with Biofilm Formation in Bacteria Isolated from Wound Infection - Prabhavati Shinde; Shraddha Jaiswal; Vidya Tale (Journal of Pure and Applied Microbiology)
Chronic wounds pose a substantial challenge to the global healthcare system. Despite the development of diverse treatments targeting various aspects of wound healing, the formidable obstacle of polymicrobial biofilm consortia persists. The biofilm matrix comprises EPS (Extracellular Polymeric Substances), mainly contains proteins, carbohydrates and eDNA (Extracellular DNA). It offers numerous advantages to microorganisms within the biofilm. The objective of this study was to evaluate the ability of bacteria isolated from wound infections to form biofilm using various methods and to analyze the composition of their EPS within the biofilm. Bacteria were isolated from wound swabs and identification was done by MALDI-TOF MS. Biofilm production was determined with the Congo red agar (CRA), crystal violet staining and microtiter plate methods. The genes involved in biofilm formation such as icaA and clfA, were detected through PCR analysis. EPS components were measured at different incubation times, with carbohydrates quantified by phenol-sulfuric acid method, proteins determined by the Lowry method, and eDNA analyzed through agarose gel electrophoresis. All bacteria showed the ability of biofilm formation and were distinguished as strong, moderate or weak biofilm makers. In the EPS, carbohydrate content increased after 72 hours of incubation, protein content was highest after 48 hours, and eDNA levels were highest after 72 hours of incubation. This study highlighted that biofilm-forming bacteria express various molecules in their EPS at different time intervals and hold promise for advancing our understanding of structural changes of biofilm and architectural integrity and functionality of matrix components.